Nobiletin from citrus peel: a promising therapeutic agent for liver disease-pharmacological characteristics, mechanisms, and potential applications - Cheng, Yongkang; Feng, Sansan; Sheng, Chuqiao; Yang, Chunfeng; Li, Yumei (Frontiers in Pharmacology, 2024)
Nobiletin (NOB) is a flavonoid derived from citrus peel that has potential as an alternative treatment for liver disease. Liver disease is a primary health concern globally, and there is an urgent need for effective drugs. This review summarizes the pharmacological characteristics of NOB and current in vitro and in vivo studies investigating the preventive and therapeutic effects of NOB on liver diseases and its potential mechanisms. The findings suggest that NOB has promising therapeutic potential in liver diseases. It improves liver function, reduces inflammation and oxidative stress, remodels gut microflora, ameliorates hepatocellular necrosis, steatosis, and insulin resistance, and modulates biorhythms. Nuclear factor erythroid 2-related factor 2 (Nrf2), nuclear transcription factor kappa (NF-κB), AMP-activated protein kinase (AMPK), peroxisome proliferator-activated receptor α(PPAR-α), extracellular signal-regulated kinase (ERK), protein kinase B (AKT), toll-like receptor 4 (TLR4) and transcription factor EB (TFEB) signaling pathways are important molecular targets for NOB to ameliorate liver diseases. In conclusion, NOB may be a promising drug candidate for treating liver disease and can accelerate its application from the laboratory to the clinic. However, more high-quality clinical trials are required to validate its efficacy and identify its molecular mechanisms and targets.